COVID-19-related patient discrimination by healthcare workers: A single- center experience - Akinbodewa, Akinwumi Ayodeji; Ige, Oluwole Olugbenga; Gbala, Michael Olumide; Akinbodewa, Gladys Oghenevo (Indian Journal of Case Reports, 2020)
Discrimination against patients, especially high-risk infectious cases, has been documented in many health-care facilities in Nigeria and abroad. This often results in suboptimal care and undesirable loss of life among such patients. Previously identified causes of this attitude include poor knowledge of the disease, perceived lack of capacity by hospital management to provide sufficient and appropriate personal protective equipment, and fear of exposure of self, colleagues, friends, and family to the infection. We hereby present three cases of suspected coronavirus disease (COVID)-19 in a tertiary health-care facility in Southwest Nigeria to highlight the risk of untimely death posed to patients with respiratory symptoms from other etiologies during the COVID-19 pandemic, need for early intervention by a senior physician and importance of adequate history taking in managing suspected cases of COVID-19.